Influence of psychological factors on self and perceived stigma and the efficacy of cognitive behaviour therapy in symptoms reduction among mentally ill patients (2012)
Majority of people who might benefit from mental health care either opt not to pursue it or do not fully adhere to treatment regimes once begun. They choose not to pursue mental health services because they do not want to be labeled a “mental patient” or suffer the prejudice and discrimination that the label entails. This study was conducted to investigate the influence of self esteem, locus of control and self efficacy on self and perceived stigma among mentally ill patients. Also, to examined the efficacy of cognitive behavioral therapy (CBT) in symptoms reduction. The first stage of the study as a cross sectional study which adopted expost-facto design. The sample size is one hundred and thirty (130 patients) with mean age of forty (16-65) and the standard deviations .456. For the intervention stage, the researcher adopted quasi-experimental design with ten (10) participants. The instrument for data collection was Rosenberg self-esteem scale, Perceived self-efficacy scale, Craig locus of control scale, Self stigma scale and perception of stigmatization scale. The result indicated that self esteem has a significant effect on self-stigma (t=5.35, df=118, p<.001). Also, there was significant effect of self-efficacy on patients self-stigma (t=2.80, df=118, p<.001). In addition, there was a significant interactive effect of self efficacy and locus of control on perceived stigma (F(1,116)=9.54, p<.001). The study was able to establish the efficacy of Cognitive behavioral therapy (CBT) in improvement of self-esteem (t=-8.67, df=18, p<.001), self efficacy (t=-9.16, df=18, p=<.001) and reduction of self stigmatization (t=8.24, df=18, p<.001). It is thereby concluded that self-esteem and self-efficacy significantly influence self-stigma. Also, there similarly, CBT also led to the reduction in self stigmatization among the patients. It is therefore recommended that certain psychological factors have been implicated in the level at which mental patients will perceive or stigmatize themselves. In addition, Cognitive behavioral therapy should be employed among mental health practitioner as a intervention package for reduction of self stigma among mentally ill patients